Development of a flexible control for a simulation model of a hybrid tug - Kallryd, Lars; Derman, Fredrik (My University, 2016)
This thesis is carried out at the request of Damen shipyards research department. As a step in the process of developing new fuel efficient hybrid tug-boats, simulation models of different hybrid system layouts is used to get a quick estimate of the performance of a complex system. In the process of building these models a time consuming part is to construct the control system. The question for this thesis is whether it is possible to find a flexible or modular control strategy that can be used for several different hybrid-system layouts. The question is limited to three specific system layouts and variants of these. By analysing a Simulink simulation model pro-vided by Damen and concluding requirements on the control, a new, flexible control with a user interface to input specific system parameters have been developed. The simulation model has then been used to verify the functionality of the new control. The model has also been used to evaluate the performance of the different systems when using energy stored in the battery. A reduction of the fuel consumption of up to 42% from a reference case is obtained. The flexible control works within the given limits and can be used for quick setup of new simulations. It is a functioning platform with large potential to make further improvements and implementing more functionality.
Keywords: Transport; Hållbar utveckling; Transportteknik och logistik; Transport; Sustainable Development; Transport Systems and Logistics